SUSTAINABLE CONSUMPTION IN WEST JAVA: GREEN BUYING INTENTIONS FROM MILLENNIALS - Diana Sari; Wa Ode Zusnita; R. Ghifari Ramadhana Agueni; Tri Febrianti (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2023)
This study will examine how sustainable consumption values, which consist of functional values, social values, and emotional values influence the purchase intention of green products. Based on the theory of consumption value, this study will examine the antecedents of green purchasing intentions among young adults (Millennials) in West Java Province, as the Province with the largest population in Indonesia. Structural equation modelling technique, Structural Equation Modelling (SEM) is applied to data collected from respondents through online surveys. Overall consumption value which consists of functional value, social value, and emotional value has an influence on the intention to buy green in generation Z and millennial generation in West Java with social value is the highest factor of consumption value which has an influence on consumption value, so that it can influence buying interest in green products in West Java. Therefore, there are several rooms for improvement in this research for further researchers. As the sample of the currents study was collected from a specific region, West Java and will have a broader results by taking larger region other than West Java.